Horse as Significant Other: Discourses of Affect and Therapy in Susan Richards’s Chosen by a Horse: How a Broken Horse Fixed a Broken Heart - Nyman, Jopi (Humanimalia, 2014)
This essay examines Susan Richards’s memoir Chosen by a Horse: How a Broken Horse Fixed a Broken Heart (2006) by focusing on its affective representation of the human-horse relationship. The discussion shows how the story of the mare Lay Me Down in Richard’s work is intricately linked with the narrator’s changing identity. It contends that this relationship, represented in the text by the use of a discourse of healing and self-regeneration, seeks to reconstruct the traumatized autobiographical subject and negotiate her identity. The close bond with between the narrator and the ailing horse shows that the two participants are involved in a joint process of identity transformation, described by Donna Haraway (2008) as becoming with another species. The essay will also suggest that the affective representation of the horse and its significance to the self-transformation of the traumatized autobiographical narrator is also part of the therapeutic discourse of contemporary American culture.